Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1096/fasebj.2019.33.1_supplement.460.13
|View full text |Cite
|
Sign up to set email alerts
|

The Cataract‐associated RNA‐Binding Protein Celf1 Post‐transcriptionally Regulates the Key Eye Transcription Factor Pax6

Abstract: The lens is a transparent tissue that focuses light on the retina allowing high‐resolution vision. Loss of lens transparency is defined as cataract, the leading cause of blindness worldwide. An estimated 25–50% of congenital cataract cases arise from underlying genetic alterations, making it important to characterize cataract‐linked genes and their pathological mechanisms.Recently, our lab demonstrated that deficiency of the gene Celf1 causes cataract in fish and mouse, indicating its conserved function in ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To achieve lens transparency, Celf1 regulates key factors, such as p27 Kip1 and Dnase2b which are necessary for degradation of nuclear and fiber cell morphology by controlling the expression level of target mRNAs, providing new Celf1-regulated mechanisms involved in lens transparency. Using immunofluorescence assays, abnormally high expression of Pax6 protein was observed in CELF1 knockdown lenses compared to control lenes, suggesting that the eye transcription factor PAX6 is a key target regulated by CELF1 in lens development [19]. In addition, Aryal et al [20] found that Celf1 could post-transcriptionally control the spatiotemporal expression of the key homeodomain transcription factors Pax6 and Prox1 in the lens development in mice.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve lens transparency, Celf1 regulates key factors, such as p27 Kip1 and Dnase2b which are necessary for degradation of nuclear and fiber cell morphology by controlling the expression level of target mRNAs, providing new Celf1-regulated mechanisms involved in lens transparency. Using immunofluorescence assays, abnormally high expression of Pax6 protein was observed in CELF1 knockdown lenses compared to control lenes, suggesting that the eye transcription factor PAX6 is a key target regulated by CELF1 in lens development [19]. In addition, Aryal et al [20] found that Celf1 could post-transcriptionally control the spatiotemporal expression of the key homeodomain transcription factors Pax6 and Prox1 in the lens development in mice.…”
Section: Introductionmentioning
confidence: 99%